The optimal resource allocation in stochastic activity networks via the electromagnetism approach - Tereso, Anabela Pereira (2004)
An optimal resource allocation approach to stochastic multimodal projects had been previously developed by applying a Dynamic Programming model, which proved to be very demanding computationally. Approximations to the initial model had been also developed, still within DP framework. Computing times were improved, but demonstrated the need for further developments. In this paper we report on the application of a recently developed technique for global optimization, the Electromagnetism Algorithm (EMA), to this problem and demonstrate its superior performance to previously attempted approximations.